As vogais médias pretônicas na variedade do interior paulista - Carmo, Márcia Cristina do [UNESP] (2013)
This work analyses the phonological behaviour of the pretonic mid-vowels in a dialect of Brazilian Portuguese in the northwest of São Paulo state. In this variety, the variable phenomenon named vowel raising can be found. Through this phenomenon, the pretonic midvowels /e/ and /o/ are pronounced, respectively, as the high vowels [i] and [u], e.g. “p[i]queno” (“small”/“little”) and “c[u]sturando” (“sewing”). Two processes can result in the application of vowel raising: (i) vowel harmony, through which there is an influence of a high vowel in the subsequent syllable, e.g. “an[i]mia” (“anemia”) and “gas[u]lina” (“gasoline”); and (ii) vowel reduction, generally related to the influence of the place of articulation of the adjacent consonant(s), e.g. “s[i]nhora” (“lady”) and “c[u]meçamos” (“we start/started”). The corpus of this study consists of spontaneous speech samples of thirty-eight interviews taken from the IBORUNA database, a result of the ALIP Project (IBILCE/UNESP – FAPESP 03/08058-6). This work follows the Theory of Linguistic Variation and Change (Labov, 1991 [1972]) and utilises the statistical package Goldvarb X for the analysis of the data. The general results highlight the relevance of vowel harmony to the application of vowel raising, as indicated by the selection of the “height of the vowel in the subsequent syllable” as the most important variable for the vowel raising of /e/ and /o/, regardless of grammatical class. Given the absence of vowel lowering in the context of pretonic mid-vowels, this variety can be grouped within the dialects spoken in southern Brazil. This work also tests two non-classical approaches of Optimality Theory (Prince; Smolensky, 1993; McCarthy; Prince, 1993): the Partial Ordering Theory (Anttila, 1997; Anttila; Cho, 1998) and the Rank-Ordering Model of EVAL (Coetzee, 2004, 2006). It is demonstrated that both perspectives cannot fully account ...